GRAMMATICAL INTRICACY AND LEXICAL DENSITY IN THE TEXTS OF ENGLISH HANDBOOK AT PRIVATE ISLAMIC JUNIOR HIGH SCHOOL LEVEL IN MEDAN - Maslathif Dwi Purnomo (UIN Sumatera Utara Medan, 2016)
Abstract: This study aimed to find out the problems occur in the grammatical complexity of the narrative and descriptive texts in English Handbook used by the Private Islamic Junior High School in Medan especially in Grade VII, VIII, and IX. The lower level should have the text written in simple sentences more than the higher one while the compound and complex sentences were suitable for the higher level. However, the findings showed that the percentage of the simple sentences used in the narrative texts of Grade VII, VIII, and IX was 33.9%, 60% and 50%. The percentage of compound sentences used in the narrative texts of Grade VII, VIII, and IX was 33.3%, 4% and 16.7% while the percentage of complex sentences used in the narrative texts of Grade VII, VIII, and IX was 27.8%, 36% and 13.3%. For the descriptive text, the percentage of simple sentences used in the descriptive texts of Grade VII, VIII, and IX was 25%, 69.2%, and 53.8%. The percentage of compound sentences used in the descriptive texts of Grade VII, VIII, and IX was 31.25%, 15.4%, and 23.1% while the percentage of complex sentences used in the descriptive texts of Grade VII, VIII, and IX was 43.75%, 15.4%, and 23.1%. Therefore, the selection of the text was grammatically inappropriate.